Performance of hot mix asphalt modified with crumb rubber tire on rut resistance [electronic resource] - 486719 Yong, Jocelyn Jia Pao; Fakulti Kejuruteraan Awam (2009)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Pengangkutan)) - Universiti Teknologi Malaysia, 2009